User requirements for elderly smart phone / Nur Hamizah Bahaman - Bahaman, Nur Hamizah (2014)
Nowadays, smart phone have become prevalent across the world. Many functions and services offered in the smart phone are important but current smart phone more convenient and user friendly to younger generation. Not to forget, Malaysia is one of the developing countries that have increasing in ageing population. However, the current trend smart phones designs are more focus to teenager and adult and elderly became a neglected user group. In addition, the current technologies do not adequately capture the smart phone pattern of the elderly and make them hurdles to adopting a smart phone. The objectives of this study are to identify usability issues that elderly faced due to smart phone and to recommend interface design for elderly smart phone. This study used two methods which are user testing and drawing method. As a result, usability issues can be identified and recommendations of user interface design for elderly smart phone main screen. The results of this study will contribute for another researcher on requirements for elderly smart phone.